Implementasi Puzzle Game pada Media Pembelajaran Aksara Sunda - Nashier, Luthfi Abdurrahman; Sutedi, Ade; Heryanto, Deni (Jurnal Algoritma, 2024)
Sundanese script is a culture that must be preserved from an early age to prevent extinction. At this time, not all Sundanese people understand Sundanese script, including students in schools from the Sundanese region, because not all schools require their students to learn Sundanese script. However, in fact there are deficiencies in teaching and learning activities for Sundanese script that exist with the application of media. current learning. Learning media is a vehicle for transmitting learning messages and information. Well-designed learning media will really help students digest and understand the lesson material. The aim of this research is to apply puzzle games to Sundanese script learning media, namely to apply Sundanese script puzzle games as supporting media for Sundanese script learning in learning how to combine words into sentences and can help preserve culture, especially Sundanese script. The system development method used in this research is the Multimedia Development Life Cycle (MDLC) which consists of Concept, Design, Material Collecting, Assembly, Testing and Distribution with activities carried out including literature studies, interviews, collecting material requirements, designing, creating programs, implementation of the program into an application, as well as the alpha and beta testing process. The results of this research are Sundanese script learning media that applies the puzzle game concept as a support in learning more interesting Sundanese script. With the questionnaire results reaching a score of 92.5%, the application is suitable for use for learning media purposes in class VII Madrasah Tsanawiah (MTs) schools.